Enhancing Digital Content Creation Literacy Through Online Teacher Development Program - Rochimah, Heni; Ahmad, Masduki; Wulandari (Proceeding International Conference on Education, 2025)
Digital content creation literacy has become a crucial competency for teachers in the era of technology-driven learning. This study synthesizes findings from 15 Scopus-indexed studies focusing on the effectiveness of online teacher professional development programs in enhancing teachers' skills to design and produce digital learning products, such as interactive videos, web-based modules, and infographics. The review was conducted using the PRISMA framework, ensuring a systematic and transparent process of article identification, screening, eligibility assessment, and inclusion. The analysis reveals that online TPD is most effective when it incorporates hands-on digital product creation, combined with structured mentoring, peer feedback, and the integration of synchronous and asynchronous sessions. Programs emphasizing collaborative online communities foster continuous skill improvement and knowledge sharing among educators. Meanwhile, studies that did not center on digital product creation highlight the importance of strengthening teachers' TPACK frameworks and digital literacy foundations as prerequisites for quality content development. For the Indonesian context, the findings suggest that a blended online TPD model, integrating practice-based modules, national and local collaborative forums, AI-assisted tools, and the development of Open Educational Resources, is optimal for sustainable improvement. This review also identifies research gaps, particularly the lack of large-scale local studies and the limited evaluation of classroom-level impacts. Future research should focus on assessing the quality of teacher-created digital products and their direct influence on student learning outcomes.